Influence of oxygen on stability functional fuels sistem - Іванов, С.В.; Єфіменко, В.В.; Новікова, В.Ф.; Полякова, О.В. (Proceedings of National Aviation University (archive), 2004)
Consider influence of dissolved oxygen on functional properties of jet fuels: thermooxidativ stability, fire-explosive hazards, cavitational and aniwear.